Scorpions from Ceará State, Brazil: Distribution and ecological comments - Errata - Braga, Jacqueline Ramos Machad (2022)
An error in Figure 2 of the work: Braga JRM, Ramalho RD, Sousa JCC de, Almeida IL de. 2022. Scorpions from Ceará State, Brazil: Distribution and ecological comments. Revista Peruana de Biología. 29(1):e21205–e21205. https://doi.org/10.15381/rpb.v29i1.21205Due to an editorial mistake, the latest authors version of figure 2 was not considered. The correction refers to the image of Tityus serrulatus Lutz & Mello, 1922. Image: Relrison Dias.The article files that indicate in the dates of the editorial process: “Correction [Fig 2]: 05/10/2022”, already include the change